Pengaruh kinerja rentabilitas dan risiko usaha terhadap skor kesehatan bank umum swasta nasional devisa di Indonesia - Dinda Krisna Dewiyanti; Herizon Herizon (Journal of Business & Banking, 2018)
The purpose of this research is to analyze the influence ofROA, ROE, NIM, CKPN Credit, NPL, IRR, PDN, BOPO, FBIR, and LDR either simultaneously or partially towards Bank’s Determining Health Score. Population used in this research was National Private Foreign Commercial Bank in Indonesia. The sampling technique based on purposive sampling technique. The data was a secondary data. Samples were used documentation data. This research used Multiple Regression Analysis (MRA). Hypothesis test result, it found that ROA, ROE NIM, CKPN Credit, NPL, IRR, PDN, BOPO, FBIR and LDR have a significant influence on Determining Health Score of National Private Foreign Commercial Bank in Indonesia. While it means on partially that ROA has no positive significant effect, ROE has a positive significant effect, NIM has no negative significant effect, CKPN Credit has no positive significant effect, NPL has a negative significant effect, IRR has no positive significant effect, PDN has no positive significant effect, BOPO has no negative significant effect, FBIR has no negative significant effect and the last is LDR has no negative significant effect. Among all of the variables in this research, NPL is the most dominated variables on Determining Health Score of  National Private Foreign Commercial Bank in Indonesia with 11,7 percent higher than the other variables.